1994
DOI: 10.1111/j.1744-7348.1994.tb04987.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and pathogenicity of bacteria from shoot tips of the globe artichoke (Cynara scolymus L.)

Abstract: Bacteria have been isolated from shoot tips of symptomless globe artichoke plants. These were identified as Pseudomonas fluorescens, Pseudomonas marginalis, Pseudomonas spp., Serratia liquefaciens, Enterobacter agglomeransl Erwinia, Agrobacteriurn radiobacter, an unidentified member of Rhizobiaceae and another classified in the "corynebacteria" group. The most frequently isolated species was P. Puorescens, biovars I1 and 111. The endogenous character of these bacteria was studied in plants growing in uitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…All bacteria isolated from the in vitro cultures of nine tansy genotypes were Gram-negative which i\ consistent with previous studies showing that the majority (73-88%) of bacterial conlaminant\ in in vh-o plantlets are Gram-negative (Peiialver et al, 1994;Brunner. Echegaray & Rubluo, 1995: Buckley er nl., 1995.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…All bacteria isolated from the in vitro cultures of nine tansy genotypes were Gram-negative which i\ consistent with previous studies showing that the majority (73-88%) of bacterial conlaminant\ in in vh-o plantlets are Gram-negative (Peiialver et al, 1994;Brunner. Echegaray & Rubluo, 1995: Buckley er nl., 1995.…”
Section: Discussionsupporting
confidence: 90%
“…Delphinium, Gerbera, Hosta and Iris (Leifert, Waites & Nicholas, 1989), Galega orientalis Lam. (Valkonen et al, 1993), Cynara scolymus L. (Peiialver et al, 1994) and Mentha (Buckley et al, 1995). Several studies have shown that bacteria can colonise the vascular tissue (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intercellular spaces, vascular systems and even single cells are inhabited by several kinds of bacteria and other microbes. The asymptomatic existence of endophytic bacteria has been reported for many species, e.g., strawberry (Berg et al, 2000;Ferguson et al, 2000;Guinebretiere et al, 1999, Tanprasert andReed, 1997), tomato (Samish et al, 1961), pea (Elvira-Recuenco and van Vuurde, 2000), potato (Sturz et al, 1999), cucumber (Mahaffee and Kloepper, 1997), cotton (Chen et al, 1995), and globe artichoke (Peñalver et al, 1994). Both nonpathogenic and pathogenic bacteria can be present, causing no apparent effect on the plant (Bacon and Hinton, 1997).…”
mentioning
confidence: 99%
“…These microorganisms are introduced into in vitro cultures via explants Waites 1990, 1994), air or humans (Leifert et al 1989;Leifert and Cassells 2001). Endophytic bacteria have been reported to live in protoplast cultures of Discorea (Mantell 1997(Mantell , 1998, callus cultures of Phoenix dactylifera (Leary et al 1986), garlic (Fellner et al 1996), Norway spruce (Ewald et al 2000), Pyrethrum (Bergant et al 2005), embryogenic cultures of Norway spruce (Ewald et al 1997), meristem-tip cultures of Hydrangea (Cassells and Tahmatsidou 1996), shoot cultures of birch (Gordon and Brown 1988), Cynara scolymus (Peńalver et al 1994), mint (Reed et al 1995), Robinia pseudoacacia , Echinacea (Lata et al 2006), papaya (Thomas et al 2007a, b) and in leaves and roots of Zantedeschia aethiopica plantlets (Gunson 1992) and of Vitis vinifera (Thomas and Prakash 2004) under in vitro conditions. Endophytic fungi were found in roots and leaves of micropropagated plants from Bouteloua eriopoda and Atriplex canescens (Barrow et al 2004), in shoot tip cultures of pejibaye (de Almeida et al 2005), apple (Kolozsvári-Nagy et al 2005) and in suspension cell cultures of B. eriopoda (Lucero et al 2008).…”
Section: Introductionmentioning
confidence: 97%